2019
DOI: 10.4085/1062-6050-12-19
|View full text |Cite
|
Sign up to set email alerts
|

Athletic Trainer Services in the Secondary School Setting: The Athletic Training Locations and Services Project

Abstract: Context Previous research from a sample of US secondary schools (n = 10 553) indicated that 67% of schools had access to an athletic trainer (AT; 35% full time [FT], 30% part time [PT], and 2% per diem). However, the population-based statistic in all secondary schools with athletic programs (n = approximately 20 000) is yet to be determined. Objective To determine the level of AT services and employment status in US secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
50
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 27 publications
1
50
1
Order By: Relevance
“…Youth runners sought care from athletic trainers 2.7 times less during this period, though care seeking behavior from other providers did not change. Approximately 76% of high schools employ an athletic trainer (Huggins et al, 2019 ); however, as sports seasons were canceled early, access to these providers were potentially limited to these injured runners. Increased utilization of telemedicine by athletic trainers and other health care providers could improve access to care for this population during restrictions or in rural/remote environments (McLeod et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Youth runners sought care from athletic trainers 2.7 times less during this period, though care seeking behavior from other providers did not change. Approximately 76% of high schools employ an athletic trainer (Huggins et al, 2019 ); however, as sports seasons were canceled early, access to these providers were potentially limited to these injured runners. Increased utilization of telemedicine by athletic trainers and other health care providers could improve access to care for this population during restrictions or in rural/remote environments (McLeod et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the NATA's AMCIA recommendations and guidelines are focused on the evaluation and adjustment of medical coverage for the safety of collegiate student-athletes. However, research-O n l i n e F i r s t ers 33,34 have identified that approximately 30% of high schools in the United States lack access to athletic training services. Our results also demonstrate the level of care that high school cross-country student-athletes are not receiving when they lack access to an AT.…”
Section: Discussionmentioning
confidence: 99%
“…4,13 The latest consensus survey (2019) that assessed secondary schools' access to an AT revealed that 34% of institutions still lacked access. 14,15 This finding was almost the same as in the 2015 census survey, indicating that little growth had occurred at these institutions toward hiring an on-site health care provider to aid in the wellness and wellbeing of their student-athletes. 14 Per diem services offer a cost-effective opportunity for secondary schools to access ATs, exposing their student-athlete population to health care services and creating the possibility of a permanent position.…”
Section: Overviewmentioning
confidence: 64%
“…14 Per diem services offer a cost-effective opportunity for secondary schools to access ATs, exposing their student-athlete population to health care services and creating the possibility of a permanent position. These services are not only expanding for secondary schools due to guidelines for appropriate medical coverage 15 but are also being made available in emerging settings (eg, club sports, youth sports, and government positions). 4 In addition, researchers 1,4,16 have focused on the need for access to athletic training services by all physically active populations.…”
Section: Overviewmentioning
confidence: 99%